Fourth branchial cleft anomaly in a 7-month-old infant: A case report and literature review - Sobotková, Kateřina; Urík, Milan; Perce, Klára; Petrová, Barbora; Šikolová, Soňa; Bartoš, Michal; Jančíková, Jana; Kula, Roman; Jabandžiev, Petr (Ear, nose, & throat journal, 2025)
Fourth branchial cleft anomalies are rare head and neck congenital lesions seen in children. They present as a neck inflammatory mass and arise essentially on the left side of the neck. We report the case of a 7-month-old female with a mass of the neck associated with respiratory distress. The mass was diagnosed as an incomplete fourth branchial cleft fistula. Surgical revision of the neck abscess from an external approach and plasma coblation of the orifice in the pyriform fossa by an endoscopic approach were performed.
Keywords: Infant; Humans; lékařské ilustrace; nemoci faryngu; kojenec; branchiální krajina; krk; Abscess; Female; Medical Illustration; lidé; Pharyngeal Diseases; Fistula; Branchial Region; ženské pohlaví; Craniofacial Abnormalities; píštěle; kraniofaciální abnormality; Neck; absces